Influence of solvent composition on chiral separation of flurbiprofen and ketoprofen enantiomers using simulated moving bed chromatography - Ribeiro, António E. (2011)
Nowadays, simulated moving bed (SMB) chromatography is a well-established technique for chiral separation, as confirmed by the actual large number of published works in chemical and pharmaceutical research. Although there is a considerable number of published works on SMB technology, there are still few concerning the influence of mobile phase composition in SMB operation. This is a new topic on SMB research with very few published works, particularly those presenting not only simulation results predicted from analytical data, but also experimental results at a preparative and SMB scales. The recent outcomes of the authors are directed to the selection of the proper combination between a chiral stationary phase (CSP) and the mobile phase composition for the optimization of SMB processes. A complete study of the chiral separation of flurbiprofen and ketoprofen enantiomers, both important examples of non-steroidal anti-inflammatory drugs (NSAIDs) and frequently used in the treatment of arthritis and related diseases, by SMB chromatography is presented. This is carried out, following the findings of the previous works, and presenting new experimental results of SMB chromatography obtained at the FlexSMB-LSRE® unit, a SMB unit available at our research laboratory. These results are a progress on the topic of SMB mobile phase optimization, useful for pharmaceutical industry. A complete methodology concerning experimental, modeling and simulation results will be presented, including the enantiomers solubility and adsorption isotherm measurements, fixed-bed and SMB operations. The main focus will be placed on optimizing the mobile phase composition for chiral separation by SMB operation. These two comparative case studies will reveal that there are no predictive general rules for the optimization of mobile phase composition at a production scale and that an individualized study must be carried out, since compounds of the same family (profen enantiomers) can lead to different solutions.